Pengaruh penggunaan limbah air garam terhadap daya tetas kista artemia salina - Ndolu, Fani Melianti; Liufeto, Franchy Ch; Dahoklory, Nicodemus (Jurnal Aquatik, 2023)
Waste refers to materials that are no longer needed and, if not managed properly, can have a negative impact on society. Waste water, both from industry and households (domestic), if not managed properly, can have a negative impact on health. Salt water waste (bittern) is a type of thick liquid that is produced after the salt production process in salt ponds and can be abundant in quantity. Artemia, on the other hand, is a type of natural food that is often used in rearing shrimp and fish larvae, both in marine and fresh water throughout Indonesia. Artemia has high nutritional content, especially protein and amino acids. This study aims to assess the impact of using salt water waste on the hatchability of Artemia salina cysts. This research used a Completely Randomized Design (CRD) with four treatments repeated three times. The results showed that the use of salt water waste had a significant impact on the hatchability of Artemia salina cysts. In certain treatments, the use of 500 ml of salt water waste resulted in the highest hatchability of 7.25%, as found in the control group.